PERBEDAAN PENGETAHUAN, SIKAP DAN PERILAKU PENDERITA, KELUARGA DAN MASYARAKAT TERHADAP EPILEPSI - Suryani Gunadharma; Paranita Utama; Sobaryati Sobaryati; Ahmad Rizal; Lisda Amalia; Uni Gamayani (NEURONA, 2020)
Introduction: Achievement of epilepsy treatment depends on the understanding of patients about their disease, compliance of antiepileptic drugs,family and communities support. Gender, age, level of education, socio-cultural, economic status,and environment affect epilepsy perceptiont. Aim: To analyze the difference in knowledge, attitudes, and behavior of epilepsy patients, families and communities with different sociodemographic backgrounds. Methods: This was a cross sectional comparative analytic study. Chi-square test was used for statistical analysis. Three validated questioners were used for each groups. Results: About 264 subjects were enroled consist of 88 subjects for each groups. Men and women was almost the same amount. The most age was 36-45 years, high school was the majority of the education level. The most types of job were housewive, most of the economic level is low. There were differences in knowledge, attitudes, and behavior related to epilepsy in this 3 groups based on level of education, socio-economic and employment, except for age. Male has a better behaviour towards epilepsy . Discussion: Our results similar with the study about epilepsy patients in Ethiopia, similar with study about epilepsy families in Sudan, Korea, and similar with community study in Malaysia except for age. For counseling it’s better to separate the groups regarding level of education and sosio-economic. Keywords: Attitude, behavior, epilepsy, knowledge